Pengembangan E-Modul IPAS untuk Meningkatkan Kemandirian Belajar Siswa kelas IV SD - Jefri Dwi Putra; Ulfia Rahmi (Jurnal Family Education, 2023)
This study seeks to develop dependable, simple, and effective e-module learning resources to meet the content and media feasibility requirements for social studies class IV SD N 12 Koto Baru. This method of research and development employs the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework. Participants included teachers, students, learning experts, media experts, and material experts. Included among the research methodologies were questionnaires and evaluation instruments. The two categories of data analysis techniques are quantitative analysis techniques and qualitative analysis techniques. On the product validity test, Validator I received an average score of 4.86 ("Very Valid"), while Validator II received an average score of 4.7 ("Very Valid"). Both validators' media received identical ratings: 4.65 (Very Valid) and 4.8 (Very Valid) for validator I's media and validator II's media, respectively. The trial-based e-module practicality evaluation yielded the same score of 4.73 (Very uncomplicated) for the examination. The evaluation of the efficacy of e-module use yielded a homogeneous score of 84.35 percent and a completeness percentage of 90 percent (Very Effective). In the fourth grade of this elementary school, ADDIE was utilized to create IPAS e-modules. On the basis of the findings of the study, it was determined that IPAS fourth graders could easily utilize e-module content.